Charged particle dynamics in black hole split monopole magnetosphere - Saeed Ullah Khan; Zhi-Min Chen (European Physical Journal C: Particles and Fields, 2023)
Abstract This article examines particle dynamics and acceleration in the magnetic Penrose process (MPP) around Kerr black hole (BH) in a split monopole magnetic field. The characteristics of charged particle motion around magnetized BHs reveal four differen feasible regimes of ionized Keplerian disk behaviour: survival in regular epicyclic motion; changing into a chaotic toroidal state; collapse due to escaping along magnetic field lines and collapse due to falling into the BHs. By making use of the effective potential, we have investigated the position of stable circular orbits for both in- and off-equatorial planes. We observed that the positive magnetic field $${{\mathcal {P}}}>0$$ P > 0 increases the stability of effective potential, whereas $${{\mathcal {P}}}<0$$ P < 0 diminishes its stability. We show that ultra-efficient energy extraction from spinning supermassive BH controlled by the MPP can pay the bill. We anticipate neutral particle ionization, such as neutron beta-decay, edging closer to the BH horizon, charging protons to more than $$10^{20}$$ 10 20 eV for a supermassive BH of mass $$10^9M_{\odot }$$ 10 9 M ⊙ and a magnetic field of strength $$10^4$$ 10 4 G.